Antioxidant and Anti-tyrosinase Activities from Piper officinarum C.DC (Piperaceae) - Wan Mohd Nuzul Hakimi Wan Salleh, Farediah Ahmad, Khong Heng Yen (Journal of Applied Pharmaceutical Science, 2014)
The present study was carried out to evaluate antioxidant and anti-tyrosinase activities from Piper officinarum stems, as well as investigation of its chemical constituents. In a series of in vitro assays, antioxidant (DPPH radical scavenging and total phenolic content) and anti-tyrosinase (mushroom tyrosinase) activities of various extracts of stem were evaluated. The isolation and purification of the constituents were carried out on the extracts using various chromatographic methods and identified by direct comparison of their spectroscopic data with respective published data. The results showed that the methanol extracts showed the highest DPPH (80.0%) at 1 mg/ml, as well as total phenolic content (50.5%). Phytochemical analysis of the stem extracts have isolated five compounds identified as 4-allyl resorcinol (1), aristolactam AII (2) aristolactam BII (3), stigmast-4-en-3-one (4) and 6-hydroxystigmast-4-en-3-one (5). Compound (1), (2) and (3) showed significant activity towards DPPH radical scavenging (I%=17.3-28.1%), while (2), (3) and (4) demonstrated potent inhibitory effects against tyrosinase mushroom (I%=11.1-24.4%). The results showed that the stem extracts has significant antioxidant activity that may help to discover new chemical classes of natural antioxidant substances.
Keywords: Antioxidant,Anti-tyrosinase,Piper officinarum,Piperaceae.